Benign osteoblastoma - Mendoza, Daoiz; Cassinelli, Juan Francisco (Cirugía del Uruguay, 1970)
The paper gives an account of three cases of benign osteoblastomas; two of them are situated in the spine and the third in the calcaneus. Followi-ups between 2 and 11 years show no new symptoms of the disease. Those situated in the spine healed after curettage of the lesion. The one located in the calcaneus recurred after this therapy was applied and grew to an unusual size. which prevented the application of the conservative surgical technique for maintaining the function of the foot, which was amputated.